Composition, Combustion and Emission Characteristics of Distillation Fractions of Pyrolysis Oil of Waste Heavy-Duty Tires; Waste and Biomass Valorization; Vol. 15, iss. 6. - Kaltaev A. Albert; Slusarskiy (Slyusarsky) K. V. Konstantin Vitalievich; Gorshkov A. S. Alexander Sergeevich; Asilbekov A. Askar; Gubin A. V. Artur Vladimirovich; Larionov K. B. Kirill Borisovich (2024, 2024)
Title screen